Spatial and temporal patterns of microphytobenthos communities along the marine-terrestrial boundary in the German Wadden Sea - Yong, Joanne; Moick, Melissa; Dewenter, Jana; Hillebrand, Helmut; Kröncke, Ingrid; Lõhmus, Kertu; Pieck, Daniela; Rohde, Sven; Moorthi, Stefanie (Frontiers in Ecology and Evolution, 2022)
Microphytobenthos (MPB) are the main primary producers in shallow marine ecosystems such as the Wadden Sea. We investigated the spatial and temporal dynamics of MPB communities across the marine-terrestrial boundary over three seasons (spring, summer, fall) on three East Frisian Islands (Norderney, Spiekeroog, Wangerooge) in the German Wadden Sea. Natural transects were compared with twelve experimental islands (salt marsh vegetated versus initially bare islands) established on the tidal flats of Spiekeroog for studying dispersal-mediated community assembly. Sediment cores were taken along triplicate transects and on three elevation levels of the experimental islands, corresponding to the pioneer zone, the lower and the upper salt marsh. On both the natural transects and the experimental islands, highest MPB biomass was observed in the pioneer zone, where vegetation-driven sediment stabilization and high mud content could have promoted MPB biomass in this marine-terrestrial transition zone. On the experimental islands, MPB biomass and diversity significantly decreased with elevation regardless of season, indicating that the rarely submerged upper salt marsh level supported minimal MPB growth. MPB biomass was also higher on initially vegetated than on bare islands, which was most pronounced on the upper salt marsh level. On the tidal flat transects, MPB biomass significantly increased with elevation up to the pioneer zone before decreasing again in the lower salt marsh. Temperature, sediment water content and grain size significantly affected transect MPB biomass. MPB diversity, on the other hand, was not related to elevation, but rather determined by temperature, mean grain size and mud content. Our study suggests that extending MPB studies into the “terrestrial” domain of salt marshes enhances our understanding of the microalgae-plant interaction in this important boundary zone.